Comparison of combined suprascapular and axillary nerve pulsed radiofrequency and nerve block for the treatment of primary frozen shoulder: a prospective cohort study - Yue Wu; Jiangyou Huang; Weibo Zhang; Suming Tian; Gang Chen (Annals of Medicine)
Objectives To compare the effects of pulsed radiofrequency (PRF) and block of the suprascapular nerve (SSN) and axillary nerve (AN) in patients with primary frozen shoulder (FS).Methods Patients with primary FS received PRF (Group P) or block (Group B). Shoulder pain during rest, activity and sleep was measured by a numerical rating scale (NRS), the Shoulder Pain and Disability Index (SPADI) was used to assess shoulder function and disability, and the passive range of motion (PROM) of the shoulder joint was measured by a digital inclinometer. Assessments were made at baseline and 2 weeks and 1, 3, and 6 months after the procedure.Results Of the 74 patients, 63 were eventually included, and a total of 3 patients were lost to follow-up. Finally, 60 patients (30 in each group) completed the final analysis. There was a significant improvement in all outcome measures from baseline to 6 months after the procedure. Compared with those in group B, the NRS scores during activity and sleep in group P decreased more at 6 months after the procedure (p = 0.005 and 0.028). SPADI total scores were lower at 3 and 6 months after the procedure (p = 0.021 and 0.001). At different time after the procedure, most of the parameters of PROM improved more in group P than those in group B (flexion at 3 and 6 months, p = 0.042 and <0.001; abduction at 3 and 6 monthse, p = 0.001 and 0.001; extension at 3 and 6 months, p = 0.038 and 0.007, internal rotation at 6 months, p = 0.015; external rotation at 1, 3, and 6 months, p = 0.002, 0.002, and 0.001, respectively).Conclusions In patients with primary FS who completed both manipulation under anesthesia and intra-articular injections, PRF with SSN and AN appears to provide better pain relief, better PROM recovery, and more shoulder function improvement than nerve block treatment.